Host-microbe multiomic profiling identifies distinct COVID-19 immune dysregulation in solid organ transplant recipients - Harry Pickering; Joanna Schaenman; Hoang Van Phan; Cole Maguire; Alexandra Tsitsiklis; Nadine Rouphael; Nelson Iván Agudelo Higuita; Mark A. Atkinson; Scott Brakenridge; Monica Fung; William Messer; IMPACC Network; et al. (Nature Communications)
Abstract Coronavirus disease 2019 (COVID-19) poses significant risks for solid organ transplant recipients, who have atypical but poorly characterized immune responses to infection. We aim to understand the host immunologic and microbial features of COVID-19 in transplant recipients by leveraging a prospective multicenter cohort of 86 transplant recipients age- and sex-matched with 172 non-transplant controls. We find that transplant recipients have higher nasal SARS-CoV-2 viral abundance and impaired viral clearance, and lower anti-spike IgG levels. In addition, transplant recipients exhibit decreased plasmablasts and transitional B cells, and increased senescent T cells. Blood and nasal transcriptional profiling demonstrate unexpected upregulation of innate immune signaling pathways and increased levels of several proinflammatory serum chemokines. Severe disease in transplant recipients, however, is characterized by a less robust induction of pro-inflammatory genes and chemokines. Together, our study reveals distinct immune features and altered viral dynamics in solid organ transplant recipients.